Rhetorical counteraction in Kenneth Burke's A Rhetoric of Motives and The War of Words. Issue 4 (2nd October 2018) - Jensen, Kyle
ABSTRACT: However esoteric Kenneth Burke's A Rhetoric of Motives seems at first glance, it remains highly relevant to our contemporary moment. As a philosophy of rhetoric that centers on the nature of human conflict, it helps audiences interpret the vicissitudes of political warfare with greater precision and insight. The value of A Rhetoric of Motives becomes even more apparent in light of its recently discovered second volume, The War of Words . Together, these two volumes offer a novel method of rhetorical counteraction that helps specialist and non-specialist audiences redress the threat of nationalistic war. Burke's approach to rhetorical counteraction is distinguished by the study of rhetorical devices across history. By approaching these devices systematically, Burke believed he could help his audience reframe their attitude toward evolving political events. The purpose of this article is to present a thorough account of Burke's method so that it can enrich how we teach and engage in public deliberation today.